2010
DOI: 10.1107/s0021889809050535
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiostructure solution by iterative phase-retrieval methods: performance tests on charge flipping and low-density elimination

Abstract: Comprehensive tests on the density‐modification methods charge flipping [Oszlányi & Sütő (2004). Acta Cryst. A60, 134–141] and low‐density elimination [Shiono & Woolfson (1992). Acta Cryst. A48, 451–456] for solving crystal structures are performed on simulated diffraction data of periodic structures and quasicrystals. A novel model‐independent figure of merit, which characterizes the reliability of the retrieved phase of each reflection, is introduced and tested. The results of the performance tests show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Additional low-density elimination iterations were performed to reduce the noise in the electron-density maps. 100 successful runs were averaged in order to generate high-quality electron-density maps (Fleischer et al, 2010).…”
Section: A1 Phase 4 Superstructure Type (I)mentioning
confidence: 99%
See 1 more Smart Citation
“…Additional low-density elimination iterations were performed to reduce the noise in the electron-density maps. 100 successful runs were averaged in order to generate high-quality electron-density maps (Fleischer et al, 2010).…”
Section: A1 Phase 4 Superstructure Type (I)mentioning
confidence: 99%
“…we used a special averaging approach based on 100 successful charge-flipping structure solutions (Fleischer et al, 2010).…”
Section: A2 Phase 8 Al 73 Fe 22 Nimentioning
confidence: 99%
“…It is an established fact that charge flipping alone provides only a relatively inaccurate approximation of the true electron density, and that further iteration steps with different density modification are needed to improve the phases (Oszlá nyi & Sü to , 2008; Fleischer et al, 2010). Fleischer et al (2010) demonstrated quantitatively that the low-density elimination (LDE) method (Shiono & Woolfson, 1992) is a suitable iteration method to improve substantially the solution obtained by charge flipping.…”
Section: Charge-flipping Algorithm For Densities Without Positivity Cmentioning
confidence: 99%
“…Unfortunately, higher approximants are rare and not every QC is accompanied by one or more ACs. The best way to solve a QC structure at present is by a combination of nD charge flipping and the nD low-density elimination approach (see, e.g., Palatinus et al, 2011;Fleischer et al, 2010; and references therein), which are direct-space phasing methods. The resulting electron-density distribution function provides the necessary information for designing a starting model for subsequent structure refinements.…”
Section: Diffractionmentioning
confidence: 99%